2017
DOI: 10.1158/1078-0432.ccr-16-2017
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Evolution after Chemoradiotherapy in Anal Squamous Cell Carcinoma

Abstract: Purpose Squamous cell carcinoma of the anal canal (ASCC) accounts for 2-4% of gastrointestinal (GI) malignancies in the US and is increasing in incidence; however, genomic features of ASCC are incompletely characterized. Primary treatment of ASCC involves concurrent chemotherapy and radiation (CRT), but the mutational landscape of resistance to CRT is unknown. Here, we aim to compare mutational features of ASCC in the pre- and post-CRT setting. Experimental Design We perform whole exome sequencing of primary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 38 publications
(43 reference statements)
5
30
0
1
Order By: Relevance
“…In this context, we conducted a large array comparative genomic hybridization analysis in treatment-naive and recurrent ASCC. Despite previous exposure to ionizing radiation and DNA-damaging cytotoxic chemotherapy, the global load of genomic alterations was high but similar between treatmentnaive tumors and recurrences, in line with the mutational burden described in whole-exome analysis of ASCC 17 and in other types of carcinoma. 18,19 Surprisingly, several individual genomic alterations were observed more frequently in the group of treatment-naive tumors.…”
Section: Discussionsupporting
confidence: 70%
“…In this context, we conducted a large array comparative genomic hybridization analysis in treatment-naive and recurrent ASCC. Despite previous exposure to ionizing radiation and DNA-damaging cytotoxic chemotherapy, the global load of genomic alterations was high but similar between treatmentnaive tumors and recurrences, in line with the mutational burden described in whole-exome analysis of ASCC 17 and in other types of carcinoma. 18,19 Surprisingly, several individual genomic alterations were observed more frequently in the group of treatment-naive tumors.…”
Section: Discussionsupporting
confidence: 70%
“…Combining checkpoint inhibition with agents that can augment the frequency of NSSMs, an approach already underway with radiation in adult cancers (Haymaker et al, 2017;Herter-Spire et al, 2016;Koller et al, 2016;Liniker et al, 2016), may hold promise for children (study planned in neuroblastoma, Clinicaltrials.gov: NCT02914405). In particular, radiation has been shown to drive the clonal evolution of cancers (Findlay et al, 2016;Mouw et al, 2016), producing neoantigenic targets for antitumor T cells (Reits et al, 2006). In addition to increasing neoantigens, radiation may increase immune activation and response to checkpoint blockade through other means.…”
Section: Figure 2 Antigenic Milieu Of Sporadic Pediatric Cancers Spmentioning
confidence: 99%
“…Identifying novel biomarkers that are associated with poor prognosis will help define the cohort of patients who merit treatment escalation. Several studies have found that HPV‐negative tumors have worse outcomes, but the role of other immunohistochemical or genomic markers is less well established . Given the viral etiology of this disease, it is perhaps not surprising that prior studies have shown that the immune microenvironment in ASCC plays an important role in disease prognosis.…”
Section: Introductionmentioning
confidence: 99%